Combination of IL-10 and IL-2 induces oligoclonal human CD4 T cell expansion during xenogeneic and allogeneic GVHD in humanized mice. Issue 4 (April 2017) - Abraham, Sojan; Guo, Hua; Choi, Jang-gi; Ye, Chunting; Thomas, Midhun Ben; Ortega, Nora; Dwivedi, Alok; Manjunath, N.; Yi, Guohua; Shankar, Premlata
Abstract: IL-10 is a crucial anti-inflammatory cytokine which can also exert a seemingly divergent immunostimulatory effects under certain conditions. We found high levels of the cytokine in a xenogeneic GVHD model where NOD-scid IL2rγcnull (NSG) mice were transplanted with human PBMCs in presence of IL-2. Presence of exogenous IL-10 altered the kinetics of IL-2 induced human T cell reconstitution in vivo, showing an initial delay, followed by rapid expansion. Further, compared to IL-2 alone, treatment with IL-2 in combination with IL-10 increased survival in most animals and completely protected ∼20% of mice from GVHD. Additionally, IL-2 induced expansion of both CD4 + and CD8 + xenoreactive T cells whereas a combination of IL-2 and IL-10 resulted in selective expansion of CD4 + T cells only. TCR Vβ repertoire analysis of CD4 + T cells showed that in contrast to IL-2 alone, simultaneous presence of both cytokines drastically reduced the Vβ repertoire of the expanded CD4 + T cells. Highly restricted Vβ usage was also observed when the cytokine combination was tested in an allogeneic GVHD model where NOD-scid IL2rγc null mice expressing HLA-DR4 (NSG-DR4) were transplanted with purified CD4 + T cells from HLA-DR4 negative donors. Taken together, our results demonstrate that IL-10 can profoundly modulate the subset composition and repertoire of responding T cells during GVHD.